Primary Care Senior Seminar: An Advanced Skills, Leadership, and Career Training Model - Isabel Edge; Ilana Simon Greenberg; Jo Marie Reilly (Journal of Medical Education and Curricular Development)
Background The traditional medical school curriculum has offered few opportunities to enhance and support interest in primary care (PC), particularly for medical students who have completed their core clinical clerkships. The Primary Care Senior Seminar (PCSS) is a 4-week course at the Keck School of Medicine for post-clerkship medical students consisting of clinical and didactic experiences, leadership training, skills-based workshops, and exploration of community-based health resources. The PCSS curriculum teaches critical PC concepts and skills to further motivate and solidify student interest in PC careers. This study examines the impact of the PCSS on medical students' knowledge and confidence in foundational PC skills and their future residency plans. Methods Thirty-six medical students enrolled in the PCSS completed a pre- and post-survey. Quantitative analysis was conducted in Qualtrics and Excel with significance at P < 0.05. Results Students participating in the PCSS gained significant knowledge and skills in foundational PC areas including patient communication, healthcare systems, preventive medicine, chronic illness management, in-office procedures, quality improvement (QI), and leadership. Additionally, participation in the PCSS appeared to support and motivate students to pursue PC careers. At the end of the course, students who entered feeling confident they would pursue a PC career remained confident in their decision, and many students who were initially undecided became more committed to PC. Conclusions The PCSS can serve as a replicable model for implementing a PC curriculum that will help medical schools train more highly skilled PC doctors and motivate undecided student to pursue PC careers.